Effective Evaluation: Improving the Usefulness of Evaluation Results Through Responsive and Naturalistic Approaches - Guba, Egon G.; Lincoln, Yvonna S. (San Francisco : Jossey-Bass Publishers, 1981)
Abstract: The central purpose of the book is to propose and describe a method of evaluation keyed directly to the concerns of those with a stake in the results through the use of naturalistic methods of inquiry. Naturalistic methods are those methods by which truths are established through a qualitative field-based inquiry rather than a predetermined experimental approach. Part One of the book is devoted to analyzing a number of models for evaluation including those advanced by Tyler, Stufflebeam (CIPP), Stake, and Scriven
Part Two is devoted to introducing and comparing the nature of various paradigms of inquiry and advocates the use of the naturalistic paradigm, rather than a scientific one for investigation of issues involving human behavior. Part Three introduces the rea der to the utilization of qualitative research methodologies. Topics covered in Part Three include the evaluator as an instrument, interviewing, observation, interpretation of nonverbal cues, and using unobtrusive means and documents. Part Four introduces the actual steps in carrying out a naturalistic, responsive evaluation and includes discussion of such issues as initiating and organizing the evaluation, identifying key issues and concerns, gathering useful information, and reporting results and recommendations
Preface -- Tables and figures -- The authors -- PART ONE: A NEW APPROACH TO EVALUATION: Comparing evaluation models -- Emergence of responsive evaluation -- Determining merit and worth -- PART TWO: THE NATURALISTIC METHOD OF INQUIRY: Advantages of naturalistic methods -- Naturalistic solutions to methodological problems -- PART THREE: IMPROVING EVALUATOR SKILLS AND TECHNIQUES: The evaluator as instrument -- Interviewing, observation, and nonverbal cue interpretation -- Using documents, records, and unobtrusive measures --Initiating and organizing the evaluation -- Identifying key issues and concerns -- Gathering useful information -- Reporting results effectively and making recommendations -- TABLES -- FIGURES
Includes bibliographical references (pages 383-410) and indexes
Also issued online
Keywords: Evaluation; Evaluation -- Methodology; Evaluation Studies as Topic -- methods; Research Evaluation - Educational Evaluation